1991
DOI: 10.1084/jem.174.4.791
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-driven bystander suppression after oral administration of antigens.

Abstract: SummarySuppression of experimental autoimmune encephalomyelitis (EAE) in Lewis rats by the oral administration of myelin basic protein (MBP) is mediated by CD8 + T cells that can be isolated from the spleens of MBP-fed animals. These cells adoptively transfer protection to naive animals subsequently immunized with MBP and complete Freund's adjuvant (CFA) and suppress in vitro MBP proliferative responses. Using a transwell system in which the modulator spleen cells from MBP-fed animals are separated by a semipe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
218
0
9

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 419 publications
(247 citation statements)
references
References 29 publications
15
218
0
9
Order By: Relevance
“…8 This mucosally generated T-cell response then acts systemically to suppress inflammation via bystander suppression at the anatomic location where the fed antigen is expressed. 9,10 Studies in a viral model of diabetes illustrate this phenomenon well. When mice in which the lymphocytic choriomeningitis virus nucleoprotein is expressed in the pancreas on the rat insulin promoter are infected systemically with lymphocytic choriomeningitis virus, antiviral immune responses cause diabetes.…”
Section: See P 1599mentioning
confidence: 85%
“…8 This mucosally generated T-cell response then acts systemically to suppress inflammation via bystander suppression at the anatomic location where the fed antigen is expressed. 9,10 Studies in a viral model of diabetes illustrate this phenomenon well. When mice in which the lymphocytic choriomeningitis virus nucleoprotein is expressed in the pancreas on the rat insulin promoter are infected systemically with lymphocytic choriomeningitis virus, antiviral immune responses cause diabetes.…”
Section: See P 1599mentioning
confidence: 85%
“…However, we [27][28][29][30] and others [34][35][36] have demonstrated that injection of a tolerated antigen results in inhibition of antibody response to a second unrelated antigen injected simultaneously. We have called this phenomenon indirect effects of the exposure to tolerated proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Dependent on the antigen dose administered there is a deletion or anergy of specific T cells, or an induction of Th2-type antigen reactive T cells. The latter cells are thought to migrate to the respective target organ, become activated upon re-encounter of antigen and exert bystander suppression of any local Th1 dependent inflammation through their release of interleukin (IL)-4, IL-10, transforming growth factor beta (TGFb) or other Th2 type mediators [12,13]. Deviation from cellular to humoral immunity after oral pretreatment with antigen has also been observed in humans [14].…”
mentioning
confidence: 99%